The efficacy and safety of acupuncture therapy for sciatica: A systematic review and meta-analysis of randomized controlled trails - Zhang, Zhihui; Hu, Tingting; Huang, Peiyan; Yang, Mengning; Huang, Zheng; Xia, Yawen; Zhang, Xinchang; Zhang, Xiaolin; Ni, Guangxia (Frontiers in Neuroscience, 2023)
Background and objective Sciatica is a common type of neuropathic pain disease which poses a huge financial burden to the patient. For patients with sciatica, acupuncture has been recommended as an effective method for pain relief, while there is currently a lack of sufficient evidence to support its efficacy and safety. In this review, we aimed to critically assess the published clinical evidence on the efficacy and safety of acupuncture therapy for treating sciatica. Methods An extensive literature search strategy was established in seven databases from their inception to 31 March 2022. Two independent reviewers performed the literature search, identification, and screening. Data extraction was performed on studies that meet the inclusion criteria, and a further quality assessment was performed according to the Cochrane Handbook and Standards for Reporting Interventions in Clinical Trials of Acupuncture (STRICTA) recommendations. Summary Risk ratio (RR) and standardized mean differences (SMDs) with 95% confidence interval (CI) were calculated using the fixed-effects or the random-effects model. Heterogeneity in effect size across studies was explored using the subgroup analysis and the sensitivity analysis. The quality of evidence was estimated following the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. Results A total of 30 randomized controlled trials (RCTs) involving 2,662 participants were included in the meta-analysis. The results of the integration of clinical outcomes showed that the clinical efficacy of acupuncture was superior to that of medicine treatment (MT) in improving the total effective rate (relative risk (RR) = 1.25, 95% confidence interval (CI) [1.21, 1.30]; moderate certainty of evidence), reducing the Visual Analog Scale (VAS) pain score (standardized mean difference (SMD) = −1.72, 95% CI [-2.61, −0.84]; very low certainty of evidence), increasing pain threshold (SMD = 2.07, 95% CI [1.38, 2.75]; very low certainty of evidence), and decreasing recurrence rate (RR = 0.27, 95% CI [0.13, 0.56]; low certainty of evidence). In addition, a few adverse events (RR = 0.38, 95% CI [0.19, 0.72]; moderate certainty of evidence) were reported during the intervention, which indicated that acupuncture was a safe treatment option. Conclusions Acupuncture therapy is an effective and safe treatment for patients with sciatica, and it can be considered a suitable replacement for medicine treatment (MT). However, given the high heterogeneity and a low methodological quality of previous studies, future RCTs should be well-designed according to the rigorous methodology. Systematic review registration International Platform of Registered Systematic Review and Meta-analysis Protocols (INPLASY) (https://inplasy.com/register/), identifier [INPLASY202240060].